PELATIHAN MICROSOFT WORD EXCEL DAN POWERPOINT UNTUK SISWA PKBM HARAPAN BUNDA - Simanjuntak, I.U.V.; Silalahi, L.M. (Buletin Udayana Mengabdi; Vol 24 No 2 (2025): Buletin Udayana MengabdiDO - 10.24843/BUM.2025.v24.i02.p10, 2024)
Most students who signed up for packages A, b, and c at PKBM Harapan Bunda are baby boomers far from computers and technology. Of course this is a problem, because an effective learning system is that students are used to getting information via the internet and using primary Microsoft office. Therefore, training and learning to use computers is needed, especially primary Microsoft office, namely Word, Excel, and PowerPoint. This program aims to speed up students pursuing packages A, B, and C in completing their assignments properly within a limited time. This activity was carried out in the Electrical Engineering Laboratory at Mercu Buana University, Jakarta, using the participatory action research (PAR) method. This method combines research with ongoing action to provide alternative solutions to problems faced by partners. The results of this training will help participants understand the features of Microsoft Office Word, excel, and PowerPoint so that they applies in school and work. Of the total trainees, 90% and above are satisfied with the benefits of the training. Based on the eleven questionnaire points, only under 10% were not very satisfied with the benefits of the activity because understanding a new technology in a short time was not easy. Keywords:   Ms. Word; Ms. Excel; Ms. PowerPoint; PKBM Harapan Bunda